1991
DOI: 10.1192/s0007125000296232
|View full text |Cite
|
Sign up to set email alerts
|

Buspirone: A Worldwide Update

Abstract: Buspirone is an anxiolytic drug from the azapirone family of molecules. It differs chemically and pharmacologically from the benzodiazepines. Although its profile of efficacy is comparable with that of benzodiazepines, it produces less drowsiness, less psychomotor impairment, less alcohol potentiation, and has less potential for addiction or abuse. Buspirone also appears to have efficacy in major depressive disorders, in comparison with placebo, but its activity in panic disorders is less impressive. It may di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Buspirone is an anxiolytic that has been in clinical use for some years. It has presynaptic agonistic and postsynaptic partial agonistic properties at the 5-HT 1A -receptor (for further description, see Napoliello and Domantay. 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Buspirone is an anxiolytic that has been in clinical use for some years. It has presynaptic agonistic and postsynaptic partial agonistic properties at the 5-HT 1A -receptor (for further description, see Napoliello and Domantay. 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The delayed onset of Alcohol ClIn Exp Res, Vol 23, No 5, 1999: pp 822-827 action of the anxiolytic effect (Napoliello and Domantay, 1991) means at least a 2-week treatment period before this effect can be evaluated, with a drug that has effects on ethanol intake that are not presently well understood.…”
mentioning
confidence: 99%
“…Buspirone is an anxiolytic drug with mainly presynaptic agonistic and postsynaptic partial agonistic properties at the 5-HTl A-receptors (Napoliello and Domantay, 1991). Clinical trials have shown a beneficial effect of buspirone after ethanol withdrawal, especially in anxious alcoholics (Bruno, 1989;Tollefson et al, 1992;Olivera et al, 1990;Kranzler and Meyer, 1989).…”
mentioning
confidence: 99%
“…One reason to carefully establish the effects of buspirone on ethanol intake, beside its potential usefulness in the treatment of alcoholism, is that buspirone is given to alcoholics for the treatment of anxiety. The delayed onset of action of the anxiolytic effect (Napoliello and Domantay, 1991) means at least a 2-week treatment period before this effect can be evaluated, with a drug that has effects on ethanol intake that are not presently well understood.…”
mentioning
confidence: 99%